The Effect of Breast Care on the Smoothness of Breast Milk in Postpartum Mothers - Mardjuky, Mariyati; Astuti, Asih Dwi (UNIMUS Web Conferences, 2026)
Background: Breast milk (ASI) is the primary and optimal source of nutrition for infants during the first six months of life. However, many mothers do not provide exclusive breastfeeding due to perceived insufficient milk production, often indicated by frequent infant crying, which leads to early supplementation with formula milk. Inadequate breast milk flow is a major factor contributing to early cessation of breastfeeding and suboptimal infant growth, highlighting the need for effective interventions to improve lactation. Objective: This study aimed to analyze the difference in breast milk flow before and after the application of breast care in postpartum mother. Method: This study employed a quasi-experimental design with a one-group pretest– posttest approach. The sample consisted of 15 postpartum mothers in the working area of the Piru Health Center, selected using total sampling. Breast milk flow was measured before and after the intervention. Data were analyzed using the Wilcoxon test, with ethical principles applied throughout the research process. Results: The findings showed a significant difference in breast milk flow before and after the application of breast care, with a ρ value of 0.005 (p < 0.05). Discussion: The improvement in breast milk flow after breast care can be explained by stimulation of the breast tissue, which enhances blood circulation and triggers the release of prolactin and oxytocin hormones, thereby facilitating milk production and ejection. These results are consistent with existing lactation theories that support breast care as an effective non-pharmacological intervention. Conclusion: Breast care has a positive effect on improving the smooth flow of breast milk in postpartum mothers and can be recommended as a supportive intervention to promote exclusive breastfeeding in the Piru Health Center working area.